The chemical profile of active fraction of Kalimeris indica and its quantitative analysis. (31st March 2020) - Huang, Wenping; Wen, Zhiqi; Wang, Qi; Chen, Renhao; Li, Zhifeng; Feng, Yulin; Yang, Shilin
Abstract: Kalimeris indica (L) Sch‐Bip is a medicinal plant used by the Miao ethnic group in the Guizhou province of China. It is widely used as a fresh vegetable to treat colds, diarrhea and gastric ulcers. However, few studies have been conducted on the mechanism of its effect on colds, and its quality control. The anticomplement and antitussive activities of different polar extracts of K. indica were evaluated. Fifty‐nine compounds, mainly including phenols and flavonoids, were identified in K. indica extract by ultra‐high‐performance liquid chromatography quadrupole time‐of‐flight tandem mass spectrometry. A method was established through ultra‐high‐performance liquid chromatography with a photodiode array to simultaneously determine the anticomplement and antitussive activity of five compounds in K. indica combining chemical identification with chemometrics for discrimination and quality assessment. Also, 3, 5‐dicaffeoylquinic acid and 4, 5‐dicaffeoylquinic acid exhibited significantly higher anticomplementary activity than the other three compounds. The quantitative data were further analyzed by principal component analysis and orthogonal partial least‐squares discriminant analysis. Heatmap visualization was conducted to clarify the distribution of the major compounds in different geographical origins. Screening pharmacological activities by a combination of chemometrics and chemical identification might be an effective method for the quality control of K. indica .